2022
DOI: 10.3390/rs14051266
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Factors and Spatial Heterogeneity of Land Surface Temperatures in Urban Areas: A Case Study in Fuzhou, China

Abstract: The urban heat island (UHI) phenomenon caused by rapid urbanization has become an important global ecological and environmental problem that cannot be ignored. In this study, the UHI effect was quantified using Landsat 8 image inversion land surface temperatures (LSTs). With the spatial scale of street units in Fuzhou City, China, using ordinary least squares (OLS) regression, geographically weighted regression (GWR) models, and multi-scale geographically weighted regression (MGWR), we explored the spatial het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Meanwhile, previous studies have mainly investigated the model's fitting condition for the surface temperature in summer, meaning there is a lack of studies reported for other seasons [34,35]. This paper's results indicate that the surface temperature and spatial morphological parameters of Tianjin's old urban area have significant spatial non-smoothness, that the MGWR model's fit performance is better than the GWR model's in several seasons, and that these results are similar to those Basu [22] and Yang [36], where the summer fit superiority was higher than 0.75. The study by Liu [37] on the central city of Wuhan's surface temperature also proved the MGWR model's excellent performance.…”
Section: Does Mgwr Provide a New Perspective For Urban Thermal Enviro...mentioning
confidence: 59%
“…Meanwhile, previous studies have mainly investigated the model's fitting condition for the surface temperature in summer, meaning there is a lack of studies reported for other seasons [34,35]. This paper's results indicate that the surface temperature and spatial morphological parameters of Tianjin's old urban area have significant spatial non-smoothness, that the MGWR model's fit performance is better than the GWR model's in several seasons, and that these results are similar to those Basu [22] and Yang [36], where the summer fit superiority was higher than 0.75. The study by Liu [37] on the central city of Wuhan's surface temperature also proved the MGWR model's excellent performance.…”
Section: Does Mgwr Provide a New Perspective For Urban Thermal Enviro...mentioning
confidence: 59%
“…GWR is a local modeling tool based on the optimization of global regression models, which complements the global model by providing a set of coefficients for each geographic unit to determine the spatial variability of the observations [ 38 ]. GWR was used to explore the spatial heterogeneity of risk factors in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The OLS model is a global regression model applied to evaluate the relationship between two or more elements. The advantage of the OLS model is that it minimizes the sum of squares of the residuals for all observations (Yang et al, 2022). This study initially explored the factors influencing the spatial layout of family farms using the OLS model.…”
Section: Ordinary Least Squares Regression (Ols)mentioning
confidence: 99%
“…To determine the best bandwidth value, we adopted the corrected Akaike information criterion (AICc) to search for the best value (Yang et al, 2022).…”
Section: Geographically Weighted Regression (Gwr)mentioning
confidence: 99%